Lung mucosal immunity to NTHi vaccine antigens: Antibodies in sputum of chronic obstructive pulmonary disease patients - Federica Baffetta; Cecilia Buonsanti; Luca Moraschini; Susanna Aprea; Martina Canè; Stefano Lombardi; Mario Contorni; Simona Rondini; Ashwani Kumar Arora; Monia Bardelli; Oretta Finco; Davide Serruto; et al. (Human Vaccines & Immunotherapeutics)
Chronic obstructive pulmonary disease (COPD) is a common chronic respiratory illness in older adults. A major cause of COPD-related morbidity and mortality is acute exacerbation of COPD (AECOPD). Bacteria in the lungs play a role in exacerbation development, and the most common pathogen is non-typeable Haemophilus influenzae (NTHi). A vaccine to prevent AECOPD containing NTHi surface antigens was tested in a clinical trial. This study measured IgG and IgA against NTHi vaccine antigens in sputum. Sputum samples from 40 COPD patients vaccinated with the NTHi vaccine were collected at baseline and 30 days after the second dose. IgG and IgA antibodies against the target antigens and albumin were analyzed in the sputum. We compared antibody signals before and after vaccination, analyzed correlation with disease severity and between sputum and serum samples, and assessed transudation. Antigen-specific IgG were absent before vaccination and present with high titers after vaccination. Antigen-specific IgA before and after vaccination were low but significantly different for two antigens. IgG correlated between sputum and serum, and between sputum and disease severity. Sputum albumin was higher in patients with severe COPD than in those with moderate COPD, suggesting changes in transudation played a role. We demonstrated that immunization with the NTHi vaccine induces antigen-specific antibodies in sputum. The correlation between IgG from sputum and serum and the presence of albumin in the sputum of severe COPD patients suggested transudation of antibodies from the serum to the lungs, although local IgG production could not be excluded.Clinical Trial Registration: NCT02075541